The anti SARS-CoV-2 activity of nanofibrous filter materials activated with metal clusters. (January 2023) - Thomberg, T.; Bulgarin, H.; Lust, A.; Nerut, J.; Koppel, M.; Romann, T.; Palm, R.; Månsson, M.; Flores March, N.M.; Junninen, H.; Külaviir, M.; Paiste, P.; et al.
Abstract: Nanofibrous filter materials were prepared by electrospinning a solution of 28 wt% poly(vinylidene fluoride) in N, N-dimethylacetamide with and without the addition of 2 wt% AgNO3, Cu(NO3 )2 ·2.5H2 O or ZnCl2 . X-ray diffraction, scanning electron microscopy with energy dispersive X-ray spectroscopy, inductively coupled plasma mass spectroscopy, thermogravimetric analysis, contact angle measurement, nitrogen sorption, and mercury intrusion porosimetry methods were used for the characterization of physical structure as well as the chemical composition of the electrospun materials. Particle filtration efficiency and antiviral activity against the SARS-CoV-2 alpha variant were tested in order to estimate the suitability of the prepared electrospun filter materials for application as indoor air filtration systems with virucidal properties. All filter materials prepared with salts demonstrated very high particle filtration efficiency (≥98.0%). The best antiviral activity was demonstrated by a material containing Cu(NO3 )2 ·2.5H2 O in the spinning solution, which displayed the decrease in the number of infectious virions by three orders of magnitude after a contact time of 12 h. Materials with the addition of AgNO3 and ZnCl2 decreased the number of infectious virions after the same contact time by only ∼8 and ∼11 times, respectively. Graphical abstract: Image 1 Highlights: Ag, Zn and Cu containing fibrous materials were prepared by electrospinning method. Ag, Zn and Cu nanoclusters were uniformly distributed in fibrous filter materials. Ag, Zn and Cu clusters containing material showed very high filtration efficiency. Cu containing material showed very high virudical activity against SARS-CoV-2.